Pandangan Ahl Al-Sunnah Wa Al-Jama’ah terhadap Ayat-ayat Al-Quran Mengenai Hari Kiamat: The Perspective of Ahl al-Sunnah wa al-Jama‘ah on the Qur’anic Verses Concerning the Day of Judgment. - Chamdar Nur; Sohrah, Sohrah; Aisyah Arsyad (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
According to the perspective of Ahlus Sunnah wal Jama'ah, belief in the Day of Judgment is an essential aspect that affirms its certainty despite the unknown timing of its occurrence. This study aims to analyze the concept of the Day of Judgment according to Ahlus Sunnah wal Jama'ah, identify Qur'anic and Hadith-based evidence describing the signs of its arrival, and examine its impact on shaping the behavior of a Muslim. This research employs a qualitative-descriptive method with a library research approach, utilizing primary sources such as Tafsir Ibnu Kathir, Sahih Bukhari, and Sahih Muslim. The results show that the Day of Judgment is characterized by major and minor signs, as mentioned in various texts, including the spread of trials, ignorance, and rampant immorality. Ahlus Sunnah wal Jama'ah views belief in the Day of Judgment as a motivation to increase good deeds, abandon sin, and strengthen piety toward Allah Swt.. A correct understanding of the Day of Judgment not only solidifies one's creed but also encourages introspection and spiritual preparation for every Muslim. Thus, this study is expected to contribute scientifically by enriching Islamic insights and strengthening the understanding of the Muslim creed in accordance with the teachings of Ahlus Sunnah wal Jama'ah.